PHOSALONE TOXICITY ON THE MOVEMENTS AND FEEDING BEHAVIOUR OF RANA TIGRINA (DAUDIN) - ANTONY, A. JOSEPH; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
Effects of subacute doses of phosalone on feeding movements and behaviour of R. tigina were determined. Normal frogs exhibited three types of jumps (short, intermediate and long). The frequency of jumps and the distance covered were reduced in intoxicated frogs. The toxic effects on central nervous system (CNS) which co-ordinate the movements may be involved in changes in movements and feeding behaviour of frogs.